2019
DOI: 10.5380/raega.v46i1.52552
|View full text |Cite
|
Sign up to set email alerts
|

Expansão Urbana E Impactos Ambientais Na Zona Costeira Norte Do Município De São Luís (Ma)

Abstract: Este estudo tem por finalidade analisar a alteração do uso e ocupação da Zona Costeira Norte de São Luís(MA) e identificar os principais impactos ambientais que surgiram a partir da transformação do espaço natural desta região verificando as normas e diretrizes estabelecidas nos instrumentos de gestão urbana ( lei de Zoneamento, Parcelamento, Uso e Ocupação do Solo, Plano Diretor e a lei Orgânica de São Luís). Para a análise  da alteração do uso e ocupação foi feito a classificação de imagens de satélite, fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
1
2
0
5
Order By: Relevance
“…The low quality of water is shown by the presence of unsuitable points for bathing since 2015, when the State Secretary of Environment started monitoring the beaches of São Luís (Maranhão 2020). This enrichment process has already been reported for São Marcos beach (Masullo 2016, Silva et al 2009, 2013, Trindade et al 2011 and has also been observed in other beaches of São Luís (Feres et al 2008, Silva et al 2008, Serra & Farias Filho 2019, Rodrigues et al 2020.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The low quality of water is shown by the presence of unsuitable points for bathing since 2015, when the State Secretary of Environment started monitoring the beaches of São Luís (Maranhão 2020). This enrichment process has already been reported for São Marcos beach (Masullo 2016, Silva et al 2009, 2013, Trindade et al 2011 and has also been observed in other beaches of São Luís (Feres et al 2008, Silva et al 2008, Serra & Farias Filho 2019, Rodrigues et al 2020.…”
Section: Discussionsupporting
confidence: 76%
“…occurred only in upper mesolittoral, where the traffic of vehicles is less (and consequently the sediment is less compacted) compared to others (Serra & Farias Filho 2019). The sediment compaction causes a decline in the benthic communities infaunal, due to the decrease in the size of pores, which in turn, decreases the humidity and oxygen supply (Santos & Ferreira 2019).…”
Section: Polychaetamentioning
confidence: 99%
“…In São Luís, capital of the state of Maranhão, the intense and disordered process of urban expansion, fueled by real estate speculation and irregular occupations, has intensified this issue 15 . Urban waste collection is precarious and dumps are present throughout the city 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Em São Luís, capital do estado do Maranhão, o intenso e desordenado processo de expansão urbana, alimentada pela especulação imobiliária e por ocupações irregulares, tem intensificado essa problemática 15 . A coleta de lixo urbana é precária e com presença de lixões em toda a cidade 16 .…”
unclassified